AI enabled pneumonia detection and diagnosis based on the concatenation approach: A framework for healthcare sustainability - Malla, Prince Priya; Sahu, Sudhakar; Tadeusiewicz, Ryszard (1947- ); Pławiak, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
Early detection and diagnosis of pneumonia play a significant role in saving human life. However, detection of pneumonia from chest X-ray images with the help of radiologists is a time-consuming task. Thus, the development of an appropriate artificial intelligence (AI) enabled model for the precise detection of pneumonia becomes an important research topic. In this aspect, we develop an automated transfer learning-based pneumonia detection framework using a feature concatenation approach.
Keywords: artificial intelligence; healthcare; medical imaging; pneumonia detection; transfer learning; sustainability